Odpowiedź :
b. 6-(-7)×(-2)÷-4=6-14÷4=6+3,5=9,5
c. (-2-4)×(-6)÷(-3)²=-6x(-6)÷9=36÷9=4
d. (-3)×(-2-10)-5÷7-9=(-3)x(-12)-5÷7-9=36-5/7-9=27-5/7=26 2/7
e. (-2)³+45÷(-3²)=-8+45÷9=-8+5=-3
g. (-2)×1-4÷4=-2-1=-3
c. (-2-4)×(-6)÷(-3)²=-6x(-6)÷9=36÷9=4
d. (-3)×(-2-10)-5÷7-9=(-3)x(-12)-5÷7-9=36-5/7-9=27-5/7=26 2/7
e. (-2)³+45÷(-3²)=-8+45÷9=-8+5=-3
g. (-2)×1-4÷4=-2-1=-3
b) =6-14÷-4= 6-(-3,5)= 9,5
c) =(-6)x(-6)÷9= 36÷9= 4
d) =(-3)x(-12)-5÷7-9= 36-5/7-9= 26 i 2/7 (2/7- ulamek)
e) =(-8)+45÷9= (-8)+5=-3
g) =(-2)-1= -3
c) =(-6)x(-6)÷9= 36÷9= 4
d) =(-3)x(-12)-5÷7-9= 36-5/7-9= 26 i 2/7 (2/7- ulamek)
e) =(-8)+45÷9= (-8)+5=-3
g) =(-2)-1= -3